Factors that determine the price of gold in Malaysia / Amirul Amir Apandi and Siti Norfai Rusaida Hashim - Apandi, Amirul Amir; Hashim, Siti Norfai Rusaida (2014)
This research paper intends to identify the factors that determine price of gold in Malaysia. This research consists of four independent variables which are exchange rate MYR/USD, interest rate, crude oil price and inflation rate as well as gold price plays a role as dependent variable. The data in this research are taken on monthly basis ranges from January 2009 until December 2013. The result shows that the interest rate and crude oil price have significant relationship towards gold price in Malaysia. However, exchange rate of MYR/USD and inflation rate have no significant relationship towards gold price in Malaysia. The researchers also give several points of view to assist government to improve the future gold industry in Malaysia